ANALISIS ORIENTASI BERBELANJA TERHADAP TUJUAN KONSUMEN BERBELANJA PADA SITUS E-COMMERCE DISDUS.COM - Sofiany Sofiany; Bun Sucento (Journal of Business Strategy and Execution, 2013)
This study was conducted to test the orientation shop for consumers shopping destination in the e-commerce group buying. The site for conducted research was disdus.com. There are 5 types of orientation becomes the dependent variable of this research is the orientation impulsive, brand, shopping enjoyment, convenience, and price. While the independent variables are consumers shopping destination in disdus.com site. The method used was a survey by sampling with non-probability judgmental sampling method. The test data used successfully using multilinear regression test and also test a simple linear. Multilinear test proved that all the variables that exist simultaneously affect consumers shopping destination on e-commerce sites disdus.com. While the results of simple linear test showed that all variables, except the variable impulsive, proven positive effect on consumer shopping destination on e-commerce sites disdus.com.